(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The present study tries to highlight the core issues related to the British colonization of India, Burma and Malaya. Several issues such as dislocation and displacement, exploitation of the colonized countries, rootlessness, migration and the situation of Indian soldiers in British Army are at the center of this paper. This paper, apart from the historical facts, also bring to the fore the familial relations of the fictional characters. The British attacked Burma in 1885 and forced the king of Burma to move to India with his entourage, so that they could exploit the natural resources of Burma. Soon, The British gained control on all the resources, socio, cultural, economic and political life of Burma. The intention behind sending the Indian king to Burma was also the same. This paper also tries to demonstrate how the the British Army used the Indian soldiers for their unethical deeds. These soldiers were poor farmers, workers, rickshaw-pullers who came from the villages of India to earn money. The Indian Soldiers were never given credit even if they win or lose. They were just called ‘mercenary’. These cruel ways of colonizing have been well explained in this paper with the uses of some remarkable quotations from the this novel.